Technological Approach to Education as a Pedagogical Innovation - Ismatova Nargiza Ikramovna (Zien Journals, 2022)
The article discusses the importance of the technological approach to education and the development of education, the introduction of the principles of consistency, systematization, the main changes in pedagogical activity in teaching based on innovative technologies, pedagogical methods as a result of innovative technologies in education, forms of education, modern educational technologies, technological innovations. mechanisms, teaching, modern methods and techniques of teaching, pedagogical innovations, new organizational structures in the field of education, organizational innovations and the definition of the role of learners in the organization of the educational process
Keywords: education; process; technology; approach